2009
DOI: 10.1088/0031-9155/54/20/022
|View full text |Cite
|
Sign up to set email alerts
|

Statistical LOR estimation for a high-resolution dMiCE PET detector

Abstract: We develop a statistical line of response (LOR) estimator of the three-dimensional interaction positions of a pair of annihilation photons in a PET detector module with depth of interaction capability. The three-dimensional points of interaction of a coincidence pair of photons within the detector module are estimated by calculation of an expectation of the points of interaction conditioned on the signals measured by the photosensors. This conditional expectation is computed from estimates of the probability d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…A number of studies have quantified the effects of MIPEs on system photon sensitivity and the quality of highresolution PET images, [7][8][9][10][11][12] based on either crystal configurations with the ability to record only a MIPE's center-of-mass coordinates in 2-D, 7 systems that can record individual MIPE interactions, but using crystal elements larger 1 mmϫ 1 mmϫ 1 mm, or systems with limited ability to process MIPEs for image reconstruction. [8][9][10][11][12] Different approaches have been studied in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have quantified the effects of MIPEs on system photon sensitivity and the quality of highresolution PET images, [7][8][9][10][11][12] based on either crystal configurations with the ability to record only a MIPE's center-of-mass coordinates in 2-D, 7 systems that can record individual MIPE interactions, but using crystal elements larger 1 mmϫ 1 mmϫ 1 mm, or systems with limited ability to process MIPEs for image reconstruction. [8][9][10][11][12] Different approaches have been studied in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Different approaches have been studied in Refs. 7-12 for identifying the first interaction in MIPEs, these include positioning MIPEs ͑i͒ at the energy-weighted spatial mean, ͑ii͒ at the interaction with the highest or second highest energy, ͑iii͒ at the interaction closest or farthest from the scintillator-photodetector interface, ͑iv͒ at the interaction most likely to be the first according to Compton kinematics or Klein-Nishina differential cross section ͑as well as hybrids thereof͒, and ͑v͒ using a maximum likelihood Bayesian estimator based on photon interaction kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…e k is the computed estimated energy of a photon after the k-th interaction at position a k , and e 0 is assumed to be 511 keV. The detail of computing the probability for an interaction sequence could be found in [3].…”
Section: A the Statistical Lor Estimation Algorithmmentioning
confidence: 99%
“…In order to estimate the first interaction positions of photons, a statistical LOR estimation method is proposed in [3]. It uses a Bayesian estimator for determining a LOR by estimating three-dimensional interaction positions of a pair of annihilation photons.…”
Section: Introductionmentioning
confidence: 99%
“…As we developed our dMiCE and cMiCE detector concepts [1,2], we found that our existing electronics was inadequate to the task and launched a design effort we have termed our Phase II electronics [3]. Here we report on the implementation and evolution of the Phase II system as a basic building block for a wide variety of data acquisition tasks.…”
Section: Introductionmentioning
confidence: 99%